2020
DOI: 10.2147/ijgm.s263665
|View full text |Cite
|
Sign up to set email alerts
|

<p>Community’s Knowledge of COVID-19 and Its Associated Factors in Mizan-Aman Town, Southwest Ethiopia, 2020</p>

Abstract: Background: Coronaviruses are a large group of viruses that are common throughout the community. They are associated with mortality, hospitalization, substantial extra costs and lower patient's quality of life. Thus, this study aimed to assess the community's knowledge of COVID-19 and associated factors in Mizan-Aman town, southwest Ethiopia. Methods: Community-based cross-sectional study design was conducted among the community of Mizan-Aman from April 14 to May 14, 2020. A systematic sampling technique was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
4
11
1
Order By: Relevance
“…From our study, a good knowledge score was recorded for 69.8% (95% CI: 65.2-73.9) of taxi drivers. The result is in line with findings of some other studies conducted in Ethiopia 70% and 64.6% [31,32] and Uganda 69% [33]. It is much higher than the findings from other Ethiopian studies 37.59%, 41.3%, 42.9%, 45.89% and 60.5% [34][35][36][37][38], from Syria 60% [39], and from Pakistan 54.3% [40].…”
Section: Discussionsupporting
confidence: 90%
“…From our study, a good knowledge score was recorded for 69.8% (95% CI: 65.2-73.9) of taxi drivers. The result is in line with findings of some other studies conducted in Ethiopia 70% and 64.6% [31,32] and Uganda 69% [33]. It is much higher than the findings from other Ethiopian studies 37.59%, 41.3%, 42.9%, 45.89% and 60.5% [34][35][36][37][38], from Syria 60% [39], and from Pakistan 54.3% [40].…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, one article that did not report the outcome of interest (proportion of adequate knowledge, good attitude, and good prevention practice) was also excluded. 21 Finally, the final meta-analysis included 13 studies 1 , 2 , 3 , 4 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ( Figure 1 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…All 13 studies included in this review were published in 2020. Among these, only four were used community-based cross-sectional studies 3 , 22 , 26 , 27 ; the rest employed institutional-based cross-sectional study designs. Of the 13 studies, 12 reported the proportions of participants with adequate knowledge of COVID-19 in Ethiopia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though there is no similar study done anywhere about the level of community readiness toward COVID-19 prevention measures, there are studies that support the association of educational level with perception and knowledge toward COVID-19 prevention measures. For instance, the study was done in China, 18 Paraguayans 23 Egyptians, 15 Mizan Aman, 40 Arbaminch town, 27 and Northwest Ethiopia 41 showed the association of educational status with perception, attitude and knowledge of study participants toward COVID-19 prevention measures. This might be because education is the main driving force for everything which may make respondents internalize the risk analysis of the disease.…”
Section: Discussionmentioning
confidence: 99%